(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article provides a comprehensive analysis of the relevance of the discipline of book graphics in the modern educational system, examining its pedagogical, artistic, and technological importance in detail. The necessity of updating the content of this discipline and bringing it to a new stage through digital technologies, typography, and design software is scientifically substantiated. The article also highlights the significance of using modern technical tools in the educational process while preserving national artistic traditions. The research results show that the study of book graphics plays an important role in the formation of aesthetic education, the development of creative thinking, and the enhancement of visual culture.